Analisis Self Disclosure Antara Klien Dan Konselor: (Studi Komunikasi Terapeutik Antara Klien Dan Konselor Di Pusat Pembelajaran Keluarga Provinsi Sulawesi Selatan) - Indrayanti; Sennahati; Mansyur, Muhammad; Adnan, A. Evi Elvira; Nurramadhani, Rezki; Herman, Nur Apriliani (DPW FORSILADI SULSEL, 2025)
ABSTRACT. The objectives of this research are: (1) To determine the process of self- disclosure in clients during the implementation of counseling at PUSPAGA, South Sulawesi province; (2) To determine the supporting and inhibiting factors for clients to carry out self-disclosure to counselors at PUSPAGA South Sulawesi province. This research uses descriptive qualitative methods, with data collection techniques through observation and in-depth interviews with 2 counselors and 4 clients at PUSPAGA South Sulawesi Province. This method provides in-depth insight into the process of self-disclosure as well as the supporters and obstacles to client self-disclosure to counselors at PUSPAGA South Sulawesi Province. The research results show that (1) the self-disclosure process helps counselors understand the client's psychological condition more deeply, so that the intervention provided is more effective. The stages of therapeutic communication, such as pre-interaction, orientation, work, and termination, support the client's openness to the counselor and create a safe and empathetic environment. (2) Supporting factors for self-disclosure include client anxiety and the need to understand oneself, while inhibiting factors include distrust and social norms. In the context of interpersonal communication, counselors have an important role in overcoming these obstacles through a supportive approach and building a relationship of mutual trust, so that effective and therapeutic communication can be achieved. Keywords : Self-disclosure, Psychological Condition, PUSPARAGA, Interpersonal Communication.